KERJASAMA KEPOLISIAN NEGARA REPUBLIK INDONESIA (POLRI) DALAM ASEAN NATIONAL POLICE (ASEANAPOL) UNTUK MENANGANI TERORISME DI INDONESIA PERIODE 2002-2006 - P, Bima Andrianto; Windiani, Reni; P, Shary Charlotte (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2016)
Indonesia is one of the countries that had many terrorism threats in which in2002 become the appex of terrorism accident. Terrorism cases in Indonesiaare very interesting to observe because it has been decreasing gradually from2002 and ending with a decline in 2006. The Indonesian government is oftenidentified with the Police which is responsible for addressing the problems ofcrime. Polri has many roles related to terrorism mainly cooperate withinASEANAPOL. The purpose of the cooperation is to combat transnationalcrime in which terrorism is one kind of transnational crime. This researchaims is to identify the strategies and the cooperation of Polri withinASEANAPOL to combat terrorism in Indonesia from 2002 until 2006. Thisresearch uses qualitative method with descriptive- explanative type by usingliterature reviews and interviews research technique.The qualitaive method isused to oberve the natural object. The activity in qualitative method is doneinteractively and incessantly over time until complete. To answer the problem,liberal institutional theory is used in this research whilist to support thisresearch, the researcher conducted interviews to a number of institutionssuch as the Set NCB Interpol and Detachment 88. The result of this researchshows that the cooperation undertaken by Polri within ASEANAPOL tocombat terrorism indicate that the cooperation is well-succeded indicated bya decrease in cases of terrorism and followed a decrease in the number offatalities and injuries.